Evaluating Dihydroazulene/Vinylheptafulvene Photoswitches for Solar Energy Storage Applications. Issue 15 (3rd August 2017) - Wang, Zhihang; Udmark, Jonas; Börjesson, Karl; Rodrigues, Rita; Roffey, Anna; Abrahamsson, Maria; Nielsen, Mogens Brøndsted; Moth‐Poulsen, Kasper
Abstract: Invited for this month′s cover are the groups of Kasper Moth‐Poulsen at Chalmers University of Technology and Mogens Brøndsted Nielsen at University of Copenhagen. The cover image shows a conceptual graphic of molecular solar thermal energy storage system (MOST) for outdoor facilities. The Full Paper itself is available at10.1002/cssc.201700679 . Abstract : "We demonstrate how this couple shows promise as a MOST candidate in flow systems…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201700679 . View the Front Cover here:10.1002/cssc.201701336 .